Advanced teaching course for lecturers - Abang Madaud, Abang Fhaeizdhyall (UiTM Sarawak, 2021)
UiTM Sarawak has been active in contributing towards developing soft skills among members in the society. This is possible via various trainings conducted over the year. One of the recent trainings was conducted with lecturers from International College of Advanced Technology Sarawak (i-CATS) on the 10th -11th December 2020. The training involved several experienced lecturers from UiTM Sarawak: Dr Norseha Unin; Dr Sueb Ibrahim; and Associate Professor Dr Jati Kasuma, who were keen to share their experience and knowledge in teaching the current generation of students